Assessing the Relevance of Technical Education Curricula to Current Industrial Skill Demands in Tanzania: A Case Study of Civil, Electrical, and Biomedical Engineering Curriculum - Toroka, Mwanaidi Issa; Kafanabo, Eugenia (Papers in Education and Development, 2024)
This qualitative study assessed the alignment of technical education curricula with current industrial skill demands in Tanzania. Data were collected through documentary review and interviews with 34 purposively selected technical graduates. Thematic analysis was employed to analyse the data. The findings revealed persistent reliance on outdated content delivered predominantly through lecturing methods within certain parts of the curriculum. The study also identified obsolete teaching and learning facilities, such as equipment and machines. Furthermore, it highlighted discrepancies between the stated learning outcomes of the curriculum and NACTVET’s CBET standards. These findings suggest a misalignment between the curriculum and industry requirements, potentially impacting graduates’ preparedness for the workforce. Consequently, the study recommends a comprehensive curriculum review informed by a rigorous labour market analysis. To facilitate this process, NACTVET could offer training programmes for technical education institutions on developing curricula aligned with CBET standards. Keywords: implemented curriculum, learning outcomes, relevant curriculum, teaching and learning facilities, technical graduates